The correlation of central and peripheral zones in Byzantine and Russian churches: on the usability of the term “five-nave” regarding the 9th-12th c. monuments - Freze, Anna A. (Actual Problems of Theory and History of Art, 2012)
Recently the hypothesis of N. Brunov, who reconstructed some of the preserved Middle Byzantine churches of Constantinople as five-aisled, has been approved by some additional archeological evidence. The new data confirm the existence of additional structures flanking the main core of the churches. The architectural composition of the monuments and, especially, their triple arcades in the arms of the cross provide the necessary unity in the interior for the whole five-aisled structure.
Keywords: Byzantine architecture of the 9th – 12th cc; Constantinople; Old Russian architecture; five-aisled church; St. Sophia Cathedral in Kiev; N. Brunov